Juridical Analysis of Reclamated Land Rights in Batam City – Case Studies PT. Pasifik Karya Sindo - Silvia Handayani; Siti Nurkhotijah; Darwis Anatami; Nicha Suwalla; Dedy Sunarto (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
This study examines the juridical analysis of land rights over reclamation areas in Batam City, with a case study of PT. Pasifik Karya Sindo. The core issue lies in the legal status of reclaimed land, which is not yet comprehensively regulated under Indonesian law, leading to legal uncertainty for both business actors and local authorities. This research employs a normative juridical method with statutory, conceptual, and case study approaches. Data were collected through literature review, analysis of relevant legislation, and examination of legal documents. The findings indicate that reclaimed land essentially remains part of state-controlled coastal areas under the Basic Agrarian Law and sectoral maritime regulations. However, the granting of land rights over reclaimed areas requires clearer legal foundations to avoid conflicts with the principles of legal certainty and justice. The case of PT. Pasifik Karya Sindo illustrates the regulatory disharmony between the authority of the Batam Development Board and the local government, which has resulted in delays in the legalization of reclamation land rights. This study recommends regulatory synchronization between the central government, the Batam Authority, and local government, as well as the formulation of specific regulations on the management of reclamation land to ensure legal certainty and prevent future land disputes.